Schema activation strategy in reading comprehension to improve student's interest - Hidayatullah, Rizky; Saputra, Andika Ari; Amalia, Dian Risky; Hasyim, Umar Alfaruq A. (Jurnal Penelitian Ilmu Pendidikan, 2020)
This research is aimed to improve the reading comprehension through schema activation strategy. Classroom Action Research (CAR) was conducted in two cycles and each cycle consisted of four phases. They were planning, acting, observing, and reflecting. The subjects of the study were 34 students of Class VIII A of SMP Muhammadiyah 1 Godean. There were two forms of data in this study. The qualitative data were collected through observation and interview. The data were presented in the form of field notes and interview transcripts. Then, the quantitative data were collected through Pre-test, Posttest I, and Posttest II. In reference to the application of the two cycles, the results of the research revealed that use of schema activation strategy successfully improved the students"˜reading comprehension. The students"˜interest and attention in the process of teaching and learning English, especially reading improved. They were also able to explore many words related to the topic of the lesson. In relation to their comprehension of English texts, the students were able to identify main ideas and supporting details of paragraphs correctly. Strategi skema pada materi reading comprehension untuk meningkatkan ketertarikan siswa Penelitian ini bertujuan untuk meningkatkan pemahaman reading comprehension melalui penggunaan Schema Activation Strategy. Dalam melakukan penelitian ini, Peneliti menggunakan Penelitian Tindakan Kelas (PTK) sebagai metode penelitian. Penelitian dilakukan dalam dua siklus dan masing-masing siklus terdiri dari empat fase. Yaitu fase persiapan, aksi, observasi dan refleksi. Subjek penelitian adalah 34 siswa dari kelas VIII A SMP Muhammadiyah 1 Godean. Ada dua macam data yang dihimpun pada penelitian ini. Data kualitatif dikumpulkan melalui observasi dan wawancara. Kemudian data dipresentasikan dalam bentuk catatan dan transkip wawancara. Sedangkan, data kuantitatif dikumpulkan melalui Pre-Test, Post-test I, dan Post-test II. Hasil yang didapatkan setelah menerapkan dua siklus, yaitu penggunaan Schema Activation Strategy berjalan sukses meningkatkan pemahaman siswa pada bab Reading. Minat siswa dan perhatian dalam proses pengajaran dan pembelajaran bahasa Inggris, khususnya peningkatan dalam pemahaman Reading. Para siswa mampu mengeksplorasi banyak kata terkait topik pelajaran. Para siswa juga mampu memahami teks Bahasa Inggris, siswa juga mampu untuk mengindentifikasi ide pokok dan juga detail paragaraf secara benar.